LRO‐LAMP Survey of Lunar South Pole Cold Traps: Implication for the Presence of Condensed H2O. Issue 11 (3rd November 2022) - Magaña, L. O.; Retherford, K. D.; Byron, B. D.; Hendrix, A. R.; Grava, C.; Mandt, K. E.; Raut, U.; Czajka, E.; Hayne, P. O.; Hurley, D. M.; Gladstone, G. R.; Poston, M. J.; et al.
Abstract: We employ nighttime observations from the Lyman Alpha Mapping Project (LAMP) ultraviolet (UV) spectrograph onboard the Lunar Reconnaissance Orbiter to investigate the presence of condensed water ice within lunar south pole cold traps. This study incorporates LAMP observations between 2009 and 2016, which more than doubles the number of observations from previous LAMP Permanently Shadowed Regions (PSRs) studies. In this study, we focus on cold traps within five south polar craters: Faustini, Shoemaker, Haworth, Cabeus, and Amundsen. An unnamed cold trap region adjacent to Haworth and Shoemaker was also investigated. We present On‐band (148–162 nm), Edge‐band (164–173 nm), and Off‐band (175–190 nm) albedo maps at 4‐km spatial resolution and far‐UV albedo spectra of cold traps at 2‐nm spectral resolution. We find Off‐band to On‐band albedo ratios (the UV wavelength ranges with high and low H2 O ice reflectivity, respectively) within cold traps that are consistent with previous PSR studies. Spectral intimate mixture models considering 5 μm H2 O grains and a range of regolith grain sizes (20–74 μm) with porosities between 0.3 and 0.75 yields abundances of ∼0.9–4.9 wt.%, where increasing the range of H2 O and regolith grain sizes may increase the range of water abundance. We further find generally lower albedos within the cold trap regions than at the surrounding non‐cold trap regions across all wavelengths, consistent with increased regolith porosity within cold traps as suggested by Gladstone et al. (2012), https://doi.org/10.1029/2011JE003913 . Plain Language Summary: Ultraviolet (UV) observations from the Lyman Alpha Mapping Project (LAMP) in orbit around the Moon are utilized to investigate the presence of H2 O ice within areas of permanent shadow at the lunar south pole. The incorporation of more data (2009–2016) leads to increased accuracy when compared to previous LAMP investigations. We examine six regions at the lunar south pole within craters: Faustini, Shoemaker, Haworth, Cabeus, Amundsen, and an unnamed region. The ratio of two UV wavelength ranges are used as an indicator for the presence of H2 O ice and were utilized to identify regions which may contain surface ice. Models of H2 O and lunar regolith show that the observed UV spectral signatures are consistent with the presence of low amounts of water ice mixed with lunar regolith. Key Points: A new analysis of Lyman Alpha Mapping Project (LAMP) south pole measurements improves the spectral resolution to 2‐nm and incorporates additional years of acquisitions Far‐ultraviolet band ratios within cold traps are consistent with a small amount of H2 O intimately mixed with regolith and increased porosity This initial analysis of an improved LAMP spectral map data set provides the foundation for investigating additional volatile species